Cafe Atmosphere, Menu Variety, and Service Excellence toward Customer Loyalty: Suasana Kafe, Keragaman Menu, dan Pelayanan Unggul untuk Meningkatkan Loyalitas Pelanggan - Amaliyah, Rizki; Sumartik (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Customer loyalty is a critical determinant of business sustainability, particularly in the growing café industry influenced by lifestyle trends. Specific Background: Istoria Café Sidoarjo is one of many cafés competing to attract and retain customers through its unique ambiance, menu offerings, and service quality. Knowledge Gap: Previous studies often analyzed these factors separately, lacking a comprehensive approach to how they simultaneously shape customer loyalty. Aims: This research aims to analyze the relationships among café atmosphere, menu diversity, and service excellence with customer loyalty. Results: Based on 97 respondents analyzed using SPSS 26, findings show that café atmosphere and service excellence have a significant positive relationship with customer loyalty, while menu diversity shows no significant relationship. Novelty: The study reveals that even with limited menu variety, a pleasant café atmosphere and excellent service can sustain customer loyalty. Implications: The findings emphasize that maintaining service quality and ambiance consistency is more crucial than menu expansion for customer retention.Highlights: Atmosphere and service quality drive customer loyalty. Menu diversity shows no significant contribution. Consistent service and ambiance sustain customer retention. Keywords:Atmosphere; Menu Diversity; Service Excellence; Customer Loyalty; Café Management